Plasma Malondialdehid and Histopatology Healing Score Differences in Incised Old and Young Mice Zinc with Zinc Administration - Moniq W. Aryantie; Rizqy D. Monica; Andri Rezano; Sudigdo Adi; Kiki A. Rizki; Yenni Zuhairini (Journal of Medicine and Health, 2018)
Free radical plays role in wound healing. This study was conducted to determinedifferences in level of plasma malondialdehyde (MDA), and histopathological score of woundhealing by administering zinc in old and young mice. We used 24 old mice and 24 young miceincision wound model, randomized into two groups, with and without zinc administration. Wefound plasma MDA level was lower in old mice with zinc administration but not statisticallysignificant. The plasma MDA level was significantly higher by administering zinc in young mice(p=0.004). The plasma MDA level of young mice was higher than old mice in zincadministration group (p=0.010). Reepitelialization, inflammatory cells, fibroblasts andangiogenesis did not differ by administering zinc both in old mice and young mice.Reepitelialization, inflammatory cells and angiogenesis did not differ between old and youngmice in mice that were given zinc; while fibroblast of young mice is more than old mice(p=0.010). We concludedÂ  plasma MDA level is higher in young mice with zincadministration. Plasma MDA level in young mice is higher than old mice with zincadministration. Young mice with zinc administration have higher fibroblast than oldmice.Keywords: aging, free radical, histopathologic score, malondialdehid, wound healing, zinc